Development and Trial of a Paediatric Falls Screening Tool for Use in an Indonesian Context - Yulianti, Natalia Ratna; Noviandini, Dianne; Kasmirah, Kasmirah; Sudarko, Sri E. P.; Bolton, Ann; Schutz, Kobi; Hunt, Cheryl; Arthur, David G. (Department of Nursing, Faculty of Medicine, Diponegoro University, 2019)
Background: Falls in the hospital have become an important issue internationally with numerous studies and assessment tools developed with a focus mainly on elderly adults. However, little has been written about falls in children in the hospital, which reveals evidence that falls and the sequels are significant problems.Purpose: This study aimed to develop a culturally-based instrument for paediatric falls prevention.Methods: In this action research study, participants, in this case, clinical nurses, joined the researcher in progressive problem-solving in two phases, starting with composing tool items based on the previous tools and research, then conducting validity and reliability tests. The instrument, the Paediatric Risk of Falls (PROF) Scale, was developed based on a literature review, contemporary models and the local context, and its content validity. In phase two, the staff of one local hospital participated in an education programme in the use of the tool, then were involved in the screening of all falls within two months on 156 paediatric patients in the paediatric ward in a local hospital in Indonesia. Data were analysed to examine the validity and reliability of the PROF Scale using Pearson Product Moment and Cronbach's alpha coefficients.Results: Two of nine items related to medication and surgery were judged as not valid, possibly because of study parameters and technical problems in completing the items. One item on parental involvement, which was developed based on cultural practice in Central Java, was judged as a valid item. All items demonstrated acceptable reliability statistics.Conclusion: The PROF Scale demonstrates satisfactory validity and reliability as a scale for assessing falls in pediatric settings in an Indonesian context, but needs to be tested in other settings to further test validity and reliability as well as its application and acceptability.